Poznámka k Barbarasově knize o vnímání - Brabec, Jan (Lidé města, 2006)
In the “Essay on sensorily perceived objects” contained in his book Perception, R. Barbaras revisits past philosophies (empiricism, intellectualism, Husserl, and Bergson), in order to propose a philosophy of perception that would be more acceptable to him. There is still apparent effort to find some origin, bases, and original dimension of perception; thus the author in this way gradually criticizes older approaches. He reaches a concept of perception as certain interplay of the perceiving and the perceived, life and world, that he describes as a style of world being.